Epidural analgesia in labor: A narrative review. Issue 2 (21st March 2022) - Halliday, Lucy; Nelson, Scott M.; Kearns, Rachel J.
Abstract: Lumbar epidural is the most effective form of pain relief in labor with around 30% of laboring women in the UK and 60% in the USA receiving epidural analgesia. Associations of epidural on maternal, obstetric, and neonatal outcomes have been the subject of intense study, though a number of uncertainties persist. The present narrative review explores important areas of research surrounding epidural analgesia in obstetric patients including methods of initiation and administration, choice of local anesthetic solution, and the addition of adjuvants. Key meta‐analyses exploring associations of epidural analgesia on maternal and neonatal outcomes are identified and summarized. Synopsis: The present narrative review explores important areas of research surrounding epidural analgesia in labor and the effect on obstetric, maternal, neonatal, and childhood outcomes.